2006
DOI: 10.1093/aje/kwk032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subchronic and Chronic Exposure to Ambient Air Pollutants on Infant Bronchiolitis

Abstract: Ambient air pollutant exposure has been linked to childhood respiratory disease, but infants have received little study. The authors tested the hypotheses that subchronic and chronic exposure to fine particulate matter (particulate matter < or = 2.5 microm in aerodynamic diameter (PM2.5)), nitrogen dioxide, carbon monoxide, and ozone increases risk of severe infant bronchiolitis requiring hospitalization. Study subjects were derived from linked birth-hospital-discharge records of infants born in 1995-2000 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 35 publications
4
75
1
9
Order By: Relevance
“…Several studies have found an association between PM 2.5 and infant bronchiolitis, an important risk for hospitalization (Karr et al, 2007(Karr et al, , 2009a. Exposure to PM 2.5 has also been linked to low lung function in 4-year-old children in a birth cohort study in the Netherlands (Eenhuizen et al, 2012), supporting previously published studies that reported effects of PM 2.5 on lung function development, reviewed in Götschi et al (2008).…”
Section: Critical Data Gapssupporting
confidence: 77%
“…Several studies have found an association between PM 2.5 and infant bronchiolitis, an important risk for hospitalization (Karr et al, 2007(Karr et al, , 2009a. Exposure to PM 2.5 has also been linked to low lung function in 4-year-old children in a birth cohort study in the Netherlands (Eenhuizen et al, 2012), supporting previously published studies that reported effects of PM 2.5 on lung function development, reviewed in Götschi et al (2008).…”
Section: Critical Data Gapssupporting
confidence: 77%
“…5,16,23,29,32,48,64 However, some published studies found that, sometimes at low ambient O 3 levels, the relationship between various measures of morbidity and ozone concentration has a negative slope, that is, low levels of ozone appear to be more harmful than moderate values. [65][66][67] Revising the literature, Ritchie and Lenen 66 refer that no statistically significant effect for O 3 and various respiratory conditions was reported in studies undertaken in Hong Kong, London, Melbourne, Mexico, southern Ontario, Seattle, Sidney, St. John (New Brunswick), and Vancouver. The same authors found a statistically significant negative association for asthma and no relationship for other respiratory diseases on children in the Indianapolis Metropolitan Area.…”
Section: Resultsmentioning
confidence: 99%
“…13 Chronic and sub-chronic exposure to fine particulate matter, among other pollutants, was shown to be a risk factor for hospitalization due to acute bronchiolitis among children in California. 19 Using logistic regression, those authors showed that there was an association between exposure to PM 2.5 and the outcome of hospitalization due to acute bronchiolitis; and that an increase in PM 2.5 concentration of 10 µg/m 3 increased the odds of hospitalization by 9% (95% CI: 1.04-1.14). This allowed the authors to suggest that bronchiolitis was one of the adverse effects of exposure to Sheffield et al 21 in the United States found that a 7% decrease in PM 2.5 levels could result in savings of $ 15 million a year.…”
Section: Discussionmentioning
confidence: 99%